DEVELOPING QUALITY OF LEARNING IN THE PANDEMIC COVID-19 THROUGH CREATIVE AND CRITICAL THINKING ATTITUDES - Zulhafizh Zulhafizh; Silvia Permatasari (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2020)
UNIESCO and WHO records show Covid-19 has a major impact on learning activities. This condition changes the learning order of students. So the role of creative and critical thinking is needed in fostering the quality of learning. Students must maximize themselves in order to remain knowledgeable and insightful in accordance with the target learning outcomes. This observation was carried out on a sample of 73 students of the Indonesian Language and Literature Study Program. The analysis was carried out with descriptive statistics, namely substituting all respondents' answers for processing. To see the relevance and relevance of the instrument to the problem of fostering learning quality through creative and critical thinking using the Product Moment correlation method, normality with chi squared, variable role predictions through ANOVA. The results of the analysis show that the role of the creative and critical thinking variables provides a significant contribution in fostering the quality of learning up to 97.5% at an average standard of 4.168. Overall the observed variables were at a very high standard. Students have been doing creative and critical thinking activities to build or maintain the quality of their learning during the Covid-19 pandemic.